Malnutrition knowledge among nursing staff in four European countries: A cross-sectional study - Bauer, Silvia; Pospíchal, Jan; Huppertz, Viviënne; Blanař, Vít; Saka, Bulent; Eglseer, Doris (My University, 2023)
Background: Nursing staff must have sufficient knowledge in order to adequately prevent and treat malnutrition. However, only a marginal amount of information on this topic is available in the literature. Objectives: This paper provides a comparison of the malnutrition knowledge among nursing staff in Austria, the Czech Republic, the Netherlands, and Turkey and presents factors associated with the malnutrition knowledge of nursing staff. Design: A cross-sectional study was performed. Setting and participants: Nursing staff from different care settings in Austria, the Czech Republic, the Netherlands, and Turkey participated in the study. Methods: The KoM-G 2.0 (Knowledge of Malnutrition - Geriatric) questionnaire was used for data collection. Results: In total, 2056 participants from different care settings took part in the study. Between 11.7 % (Turkey) and 32.5 % (Austria) of the participants had high levels of malnutrition knowledge. The country itself was the factor most strongly associated with malnutrition knowledge. The nurses' educational level and specialised training of nursing staff were also significantly (p < 0.001) associated with malnutrition knowledge. Questions about "factors that should be considered during older persons' food intake" were most frequently answered correctly, while questions about "different aspects of nutritional screening" were less often answered correctly in all four countries. Conclusions: This study was one of the first to describe the rather low level of malnutrition knowledge among nursing staff in different countries. The country itself was identified as the factor most strongly associated with the nurses' knowledge of malnutrition, while the nursing staff's basic education as well as further training were also detected as significant factors. These results indicate that it is necessary to extend and improve (academic) nursing education and to offer specialised training programmes which may improve nutritional care across country borders over the long run.
Znalosti o podvýživě mezi ošetřovatelským personálem ve čtyřech evropských zemích: Průřezová studie
Keywords: Associated factors; Europe; Knowledge; Malnutrition; Nursing staff.; Související faktory; Evropa; Znalost; Podvýživa; Ošetřovatelský personál.